CHRONIC TOXICITY OF POLYSTYRENE MICROPLASTICS IN BLOOD AND ORGANS OF ALBINO MICE: A HISTOPATHOLOGICAL AND BIOCHEMICAL ASSESSMENT - Ifrah Zahoor; Safdar Sidra; Arshad Javid; Shahid Mehmood (Journal of Animal and Plant Sciences, 2026)
Microplastics (MPs) are emerging as a profound environmental and health hazard and their omnipresence in ecosystems endangers all life forms. This study delves into PS-MPs' repercussions on albino mice (Mus musculus), analyzing body weight and mortality, hematological parameters, and histopathological alterations in crucial organs. A total of seventy-five albino mice (n=75) were segregated into five principal groups, each comprising three subgroups, to receive oral administration of PS-MPs (0.7mm) over five weeks. The regimen included a control group (0.0mg/g) and four escalating doses for the experimental groups: 0.1mg/g (Treatment 1), 0.2mg/g (Treatment 2), 0.4mg/g (Treatment 3), and 0.8mg/g (Treatment 4). No mortality was observed in the study following exposure to PS-MPs in a 5 weeks trial. The investigation revealed a significant weight decrease in the highest dose group (Treatment 4) (P<0.05), in contrast to minor weight increases in the control, and other treatments, which were not statistically significant (P>0.05) thereby indicating association of higher doses with a decrease in overall weight of mice. Hematological assessments indicated a dose-dependent impact on liver and kidney functions, blood formation, and immune responses even at lower doses (P<0.05 for Treatment 3 and 4). Histological evaluations exhibited no changes in the control group, whereas a dosage increase led to notable tissue damage, including hemosiderosis, necrosis, congestion, vacuolization, degeneration, karyolysis, cellular hypertrophy, interstitial fibrosis, infiltration, atrophy, hyperplasia and granulation in contrast to the control animals. These pathologies correlated with significant health conditions (P<0.05 for higher dose groups), suggesting a possible link between PS-MP exposure and the development of diseases such as hepatitis, chronic granulomatous disease, and asthma. This study underscores the chronic toxicity of PS-MPs in albino mice, evidenced by hematological and histopathological disturbances that become more pronounced with increased exposure.
Keywords: Microplastics; Polystyrene; Growth alteration; Hematological system; Tissue damage; emerging contaminants